(untitled) - Moyer, Chris (Indianapolis, IN, 1996)
Que's Special Edition Using FileMaker Pro 3 for the Mac is your complete guide to building powerful databases. From new relational capabilities to automating tasks, you'll find the information you need to get to work immediately. The expert author, a national FileMaker Pro trainer for Claris, guides you through the fundamentals of database design. You'll learn how to manage data more efficiently using the new relational capability. You'll see firsthand how to automate your tasks using ScriptMaker and AppleScript. You'll find in-depth coverage of the new features, including conditional scripting, Internet networking capability, enhanced error trapping, and the latest layout tools. With expert advice and complete coverage, you'll have all the tools you need to build professional databases-and increase your productivity efficiency!
Keywords: Quản lý cơ sở dữ liệu,Database management